محاولات المدرسين في ترقية اللغة العربية بمعهد التربية الإسلامية كونتور الثامن أتشيه - Trisnady, Ivan Aulia; Dhiyaurrahman, Dhiyaurrahman; Zulhelmi, Anshar; zulkhairi, zulkhairi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
Pondok Pesantren Gontor 8 Aceh is one of the Islamic educational institutions in Indonesia that implements an Arabic learning system using modern or direct methods. The teacher at Pondok Gontor 8 is assigned to impart the Arabic language with the best possible foundation. The efforts of teachers to improve the ability to speak Arabic to students are very important. Researchers take the type of research based on field studies, or the type of research used for this research is analytical and descriptive research, which is a method that describes the condition of information and conditions related to certain problems with a qualitative approach, to get data on theoretical values, not numbers from statistics. The data in this study are analytical and descriptive, consisting of written and spoken words, as well as from observational behavior. The data needed and their sources in this study are: An overview of Arabic language learning at Pondok Pesantren Gontor 8. Among the teachers' efforts to improve the Arabic language of the Gontor 8 Islamic boarding school students are as follows: bringing teaching aids and explaining their meaning, giving and memorizing new vocabulary and arranging them into sentences, holding conversations while studying and practicing speaking Arabic in front of students. imitate new sentences and words from the teacher with the correct pronunciation of Arabic words.